(untitled) (Bangladesh Journal of Urology, 2020)
Objective: Medical expulsive therapy (MET) for urolithiasis has gained increasing attention in the last few years. MET is an excellent treatment modality for ureteric stones in the appropriately selected patients. This study was carried out to study the role of MET in the treatment of upper/middle/lower ureteric and VUJ calculi to compare the safety and efficacy of tamsulosin and tamsulosin with Deflazacort as medical expulsive therapy for ureteric stones. Materials and methods: Between July 2013 to June 2014, 105 adult patients with ureteric stones sized 5mm to 10mm were randomized equally to treatment with tamsulosin or tamsulosin with deflazacort. Therapy was given for a maximum of 6 weeks. The stone expulsion rate, mean time to expulsion (days), site of stones passed, endoscopic treatment (URS) and adverse effects of the drugs were noted. Statistical analysis was done by using student’s t-test and chi-square test. Results: Total 105 patients were included in this study. Only Tamsulosin 0.4mg once daily was given to 53 patients in group A. Fifty two patients in group B were treated with Tamsulosin 0.4mg once daily plus Deflazacort 6mg twice daily.The stone expulsion rate was 84.9% (45/53) in group A and 96.1% (50/52) in group B. Mean expulsion time (days) was shorter in group B. It was 4.96 days in group B compared with group A (8.53 days) which was highly statistically significant. Conclusion: Medical expulsive therapy (MET) for ureteric stones using tamsulosin and tamsulosin with Deflazacort is safe and efficacious. Tamsulosin with Deflazacort is very effective in expelling stones present in all the levels of the ureter. Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.67-70